Non-traditional Age Black African International Students’ Experiences: Phenomenological Heuristic Inquiry - John N. Mwaura (Adult Education Research Conference, 2008)
This paper summarizes the results of a qualitative study where the purpose was to explore the lived experiences of adjusting to U.S. culture among Black African international non-traditional age adult students while attending predominantly White higher academic institutions. Implications for faculty and higher education administration working with Black African adult international students on American university campuses are suggested.
Keywords: CRT; sociocultural; Black Africans